2019
DOI: 10.1186/s13036-019-0139-6
|View full text |Cite
|
Sign up to set email alerts
|

Modelling cardiac fibrosis using three-dimensional cardiac microtissues derived from human embryonic stem cells

Abstract: Background Cardiac fibrosis is the most common pathway of many cardiac diseases. To date, there has been no suitable in vitro cardiac fibrosis model that could sufficiently mimic the complex environment of the human heart. Here, a three-dimensional (3D) cardiac sphere platform of contractile cardiac microtissue, composed of human embryonic stem cell (hESC)-derived cardiomyocytes (CMs) and mesenchymal stem cells (MSCs), is presented to better recapitulate the human heart. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 82 publications
2
31
0
Order By: Relevance
“…Alternatively, a trans-well culture with a physical separation of two cell types allows for the study of paracrine interactions but does not include direct cell-cell signaling or the presence of native ECM. CF culture in scaffold-free, multicellular aggregates does not lead to significant proliferation of primary CF, even on the surface of the spheroid, unless stimulated by growthor other profibrotic factors [(Desroches et al, 2012;Lee et al, 2019), and own observations]. Therefore, 3D co-culture offers an option to study myocardial cells with different proliferative potential and their interactions in vitro, at baseline and in stress conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, a trans-well culture with a physical separation of two cell types allows for the study of paracrine interactions but does not include direct cell-cell signaling or the presence of native ECM. CF culture in scaffold-free, multicellular aggregates does not lead to significant proliferation of primary CF, even on the surface of the spheroid, unless stimulated by growthor other profibrotic factors [(Desroches et al, 2012;Lee et al, 2019), and own observations]. Therefore, 3D co-culture offers an option to study myocardial cells with different proliferative potential and their interactions in vitro, at baseline and in stress conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In our model, TGF-β1 induced fibrotic phenotype in cardiac microtissues, as indicated by elevated levels of fibrotic genes, secretion of procollagen I and fCFs proliferation. Previously, exogenous TGF-β1 has been shown to induce fibrosis in rat [17,18] or human [19] cardiac microtissue models. Furthermore, fibrotic phenotypes in cardiac microtissues or in biowire were also produced by collagen/fibroblast enrichment [20,21] or by constitutive activation of profibrotic pathways [22].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, transcriptome analysis showed higher sensitivity and reproducibility than proteome analysis. However, although transcriptome analysis can predict tissue-specific features, RNA-seq data do not reflect 100% of cell functions because total RNA is not translated as proteins 28 Researchers generally performed FACS analysis with CM-specific markers (cTnT) to evaluate the CM differentiation rate derived from hPSCs 29 . In this study, the CM control and CM+BMP4 groups showed 29% and 92% in FACS analysis, but HtGEP analysis showed 34.3% and 83.4% (Fig.…”
Section: Discussionmentioning
confidence: 99%